2024
DOI: 10.1186/s12889-024-18393-1
|View full text |Cite
|
Sign up to set email alerts
|

Kidney stones and dietary intake in adults: a population-based study in southwest Iran

Bahman Cheraghian,
Alipour Meysam,
Seyed Jalal Hashemi
et al.

Abstract: Background The prevalence of kidney stones is on the rise globally. Several risk factors, including lifestyle, contribute to the formation of kidney stones. Nevertheless, there is a contentious debate about the relationship between diet and kidney stones. Therefore, our study aimed to assess the relationship between macronutrients and micronutrients and the formation of kidney stones. Methods This population-based cross-sectional study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…A double-blind cross-over study was conducted on 34 patients with recurrent calcium oxalate stones to examine the effect of 1.5 L/day of a mineral water rich in bicarbonate (2673 mg/L), compared to 1.5 L/day of a mineral water with a low bicarbonate content (98 mg/L), on the risk of urinary stone formation [ 32 ]. The intake of the mineral water high in bicarbonate led to a notable rise in urine pH, citrate, and magnesium excretion when compared to the control group.…”
Section: An Explanation Of the Diet For The Kidney Stone Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A double-blind cross-over study was conducted on 34 patients with recurrent calcium oxalate stones to examine the effect of 1.5 L/day of a mineral water rich in bicarbonate (2673 mg/L), compared to 1.5 L/day of a mineral water with a low bicarbonate content (98 mg/L), on the risk of urinary stone formation [ 32 ]. The intake of the mineral water high in bicarbonate led to a notable rise in urine pH, citrate, and magnesium excretion when compared to the control group.…”
Section: An Explanation Of the Diet For The Kidney Stone Diseasementioning
confidence: 99%
“…Numerous studies have examined the fat intake of individuals with kidney stones compared to those without. Some studies have reported that the fat intake of patients with stone and controls is similar [ 32 ], while others have found that stone formers have a higher dietary fat intake [ 44 ]. Complex mechanisms have been suggested to explain how the dietary fatty acid pattern, particularly the ratio of n-6 to n-3 polyunsaturated fatty acids, may impact the risk of calcium oxalate stone formation.…”
Section: An Explanation Of the Diet For The Kidney Stone Diseasementioning
confidence: 99%